Multi-GPU Based Lattice Boltzmann Method for Hemodynamic Simulation in Patient-Specific Cerebral Aneurysm (Communications in Computational Physics, 2018)
Conducting lattice Boltzmann method on GPU has been proved to be aneffective manner to gain a significant performance benefit, thus the GPU or multi-GPUbased lattice Boltzmann method is considered as a promising and competentcandidate in the study of large-scale complex fluid flows. In this work, a multi-GPUbased lattice Boltzmann algorithm coupled with the sparse lattice representation andmessage passing interface is presented. Some numerical tests are also carried out, andthe results show that a parallel efficiency close to 90% can be achieved on a single-nodecluster equipped with four GPU cards. Then the proposed algorithm is adopted tostudy the hemodynamics of patient-specific cerebral aneurysm with stent implanted.It is found that the stent can apparently reduce the aneurysmal inflow and improve thehemodynamic environment. This work also shows that the lattice Boltzmann methodrunning on the GPU platform is a powerful tool to study the fluid mechanism withinthe aneurysms and enable us to better understand the pathogenesis and treatment ofcerebral aneurysms.